Ways to improve tumor uptake and penetration of drugs into solid tumors (2014)
The main scope of this topic is to give an update on pharmacologic and non-pharmacologic approaches to enhance uptake and penetration of cancer drugs into tumors. Inadequate accumulation of drugs in tumors has emerged over the last decade as one of the main problems underlying therapeutic failure and drug resistance in the treatment of cancer. Insufficient drug uptake and penetration is causally related to the abnormal tumor architecture. Thus, poor vascularization, increased resistance to blood flow and impaired blood supply represent a first obstacle to the delivery of antitumor drugs to tumor tissue. Decreased or even inverted transvascular pressure gradients compromise convective delivery of drugs. Eventually, an abnormal extracellular matrix offers increased frictional resistance to tumor drug penetration. Abnormal tumor architecture also changes the biology of tumor cells, which contributes to drug resistance through several different mechanisms. The variability in vessel location and structure can make many areas of the tumor hypoxic, which causes the tumor cells to become quiescent and thereby resistant to many antitumor drugs. In addition, the abnormally long distance of part of the tumor cell population from blood vessels provides a challenge to delivering cancer drugs to these cells. We have recently proposed additional mechanisms of tumor drug resistance, which are also related to abnormal tumor architecture. First, increased interstitial fluid pressure can by itself induce drug resistance through the induction of resistance-promoting paracrine factors. Second, the interaction of drug molecules with vessel- proximal tumor cell layers may also induce the release of these factors, which can spread throughout the cancer, and induce drug resistance in tumor cells distant from blood vessels. As can be seen, abnormal tumor architecture, inadequate drug accumulation and tumor drug resistance are tightly linked phenomena, suggesting the need to normalize the tumor architecture, including blood vessels, and/or increase the accumulation of cancer drugs in tumors in order to increase therapeutic effects. Indeed, several classes of drugs (that we refer to as promoter drugs) have been described, that promote tumor uptake and penetration of antitumor drugs, including those that are vasoactive, modify the barrier function of tumor vessels, debulk tumor cells, and overcome intercellular and stromal barriers. In addition, also non-pharmacologic approaches have been described that enhance tumor accumulation of effector drugs (e.g. convection-enhanced delivery, hyperthermia, etc.). Some drugs that have already received regulatory approval (e.g. the anti-VEGF antibody bevacizumab) exert antitumor effects at least in part through normalization of the tumor vasculature and enhancement of the accumulation of effector drugs. Other drugs, acting through different mechanisms of action, are now in clinical development (e.g. NGR-TNF in phase II/III studies) and others are about to enter clinical investigation (e.g. JO-1).